Answer:
The equation of line passing through points (1 , 3) and perpendicular to given line is y =
x +
Step-by-step explanation:
Given as :
The equation of line is 3 x + 2 y = 5
Or , 2 y = - 3 x + 5
Or , y =
x +
Another line is passing through point (1 , 3) and perpendicular to given line equation
Now, <u>From standard line equation</u>
i.e y = m x + c
where m is the slope of the line and c is the y-intercept
Now, comparing the given line equation with standard line equation
i.e y =
x +
So, The slope of line = m = ![\dfrac{-3}{2}](https://tex.z-dn.net/?f=%5Cdfrac%7B-3%7D%7B2%7D)
According to question
Another line is perpendicular to the given line
So, for perpendicular property, The product of the lines = - 1
Let the sloe of another line = M
So, m × M = - 1
∴ M = ![\dfrac{-1}{m}](https://tex.z-dn.net/?f=%5Cdfrac%7B-1%7D%7Bm%7D)
Or. M = ![\frac{-1}{\frac{-3}{2}}](https://tex.z-dn.net/?f=%5Cfrac%7B-1%7D%7B%5Cfrac%7B-3%7D%7B2%7D%7D)
I.e M = ![\dfrac{2}{3}](https://tex.z-dn.net/?f=%5Cdfrac%7B2%7D%7B3%7D)
So, the slope of another line = M = ![\dfrac{2}{3}](https://tex.z-dn.net/?f=%5Cdfrac%7B2%7D%7B3%7D)
Now, equation of line passing through slope M and point (1 , 3)
I.e equation of line in slope-points
So, y -
= m ( x -
)
or, y - 3 = (
) × ( x - 1 )
Or, 3 × (y - 3) = 2 × (x - 1)
Or, 3 y - 9 = 2 x - 2
Or, 3 y = 2 x - 2 + 9
Or, 3 y = 2 x + 7
∴ y =
x +
So, The equation = y =
x +
Hence, The equation of line passing through points (1 , 3) and perpendicular to given line is y =
x +
Answer